Impact of a computerized provider radiography order entry system without clinical decision support on emergency department medical imaging requests. Issue 129 (June 2016) - Claret, Pierre-Géraud; Bobbia, Xavier; Macri, Francesco; Stowell, Andrew; Motté, Antony; Landais, Paul; Beregi, Jean-Paul; de La Coussaye, Jean-Emmanuel
Highlights: The main objective of this study was to investigate the impact of implementing a computer-based order entry system without clinical decision support on the number of radiographs ordered for patients seen in the emergency department. Our results show a decrease in the number of radiographs ordered after computer-based order entry system implementation, despite an increase in the number of emergency department admissions. Our study also shows that the time interval between emergency department admission and medical imaging was not affected by this new workflow. Abstract: Background and objective: The adoption of computerized physician order entry is an important cornerstone of using health information technology (HIT) in health care. The transition from paper to computer forms presents a change in physicians' practices. The main objective of this study was to investigate the impact of implementing a computer-based order entry (CPOE) system without clinical decision support on the number of radiographs ordered for patients admitted in the emergency department. Methods: This single-center pre-/post-intervention study was conducted in January, 2013 (before CPOE period) and January, 2014 (after CPOE period) at the emergency department at Nîmes University Hospital. All patients admitted in the emergency department who had undergone medical imaging were included in the study. Results: Emergency department admissions have increased since the implementation of CPOE (5388 in the period before CPOE implementation vs. 5808 patients after CPOE implementation, p  = .008). In the period before CPOE implementation, 2345 patients (44%) had undergone medical imaging; in the period after CPOE implementation, 2306 patients (40%) had undergone medical imaging ( p  = .008). In the period before CPOE, 2916 medical imaging procedures were ordered; in the period after CPOE, 2876 medical imaging procedures were ordered ( p  = .006). In the period before CPOE, 1885 radiographs were ordered; in the period after CPOE, 1776 radiographs were ordered ( p  < .001). The time between emergency department admission and medical imaging did not vary between the two periods. Conclusions: Our results show a decrease in the number of radiograph requests after a CPOE system without clinical decision support was implemented in our emergency department.